VOR Gain Is Related to Compensatory Saccades in Healthy Older Adults - Anson, Eric R.; Bigelow, Robin T.; Carey, John P.; Xue, Qian-Li; Studenski, Stephanie; Schubert, Michael C.; Agrawal, Yuri (Frontiers in Aging Neuroscience, 2016)
Objective: Vestibulo-ocular reflex (VOR) gain is well-suited for identifying rotational vestibular dysfunction, but may miss partial progressive decline in age-related vestibular function. Since compensatory saccades might provide an alternative method for identifying subtle vestibular decline, we describe the relationship between VOR gain and compensatory saccades in healthy older adults. Methods: Horizontal VOR gain was measured in 243 subjects age 60 and older from the Baltimore Longitudinal Study of Aging using video head impulse testing (HIT). Saccades in each HIT were identified as either “compensatory” or “compensatory back-up,” i.e. same or opposite direction as the VOR response respectively. Saccades were also classified as “covert” (occurring during head movement) and “overt” (occurring after head movement). The relationship between VOR gain and percentage of HITs with saccades, as well as the relationship between VOR gain and saccade latency and amplitude, were evaluated using regression analyses adjusting for age, gender, and race. Results: In adjusted analyses, the percentage of HITs with compensatory saccades increased 4.5% for every 0.1 decrease in VOR gain (p<0.0001). Overt compensatory saccade amplitude decreased 0.6 degrees (p<0.005) and latency increased 90ms (p<0.001) for every 0.1 increase in VOR gain. Covert back-up compensatory saccade amplitude increased 0.4 degrees for every 0.1 increase in VOR gain. Conclusions: We observed significant relationships between VOR gain and compensatory saccades in healthy older adults. Lower VOR gain was associated with larger amplitude, shorter latency compensatory saccades. Compensatory saccades reflect underlying rotational vestibular hypofunction, and may be particularly useful at identifying partial vestibular deficits as occur in aging adults.